The role of external knowledge sources and organizational design in the process of opportunity exploitation - Foss, Nicolai J.; Lyngsie, Jacob; Zahra, Shaker A. (Strategic Management Journal, 2013)
Research highlights the role of external knowledge sources in the recognition of strategic opportunities but is less forthcoming with respect to the role of such sources during the process of exploiting or realizing opportunities. We build on the knowledge‐based view to propose that realizing opportunities often involves significant interactions with external knowledge sources. Organizational design can facilitate a firm's interactions with these sources, while achieving coordination among organizational members engaged in opportunity exploitation. Our analysis of a double‐respondent survey involving 536 Danish firms shows that the use of external knowledge sources is positively associated with opportunity exploitation, but the strength of this association is significantly influenced by organizational designs that enable the firm to access external knowledge during the process of exploiting opportunities . Copyright © 2013 John Wiley & Sons, Ltd.